Ferroelastic domain switching toughening in spark plasma sintered t'-yttria stabilized zirconia/La2Zr2O7 composite ceramics. Issue 15 (15th October 2017) - Wang, Yanfei; Yang, Huan; Liu, Rongjun; Cao, Yingbin; Wang, Siqing
Abstract: The poor fracture toughness of La2 Zr2 O7 hinders its practical application as a thermal barrier coating topcoat material. To toughen La2 Zr2 O7, metastable tetragonal 8 wt% yttria-stabilized zirconia ( t '-8YSZ), has been introduced into the La2 Zr2 O7 matrix by plasma spray quenching of 8YSZ powders and spark plasma sintering. An evident fracture toughness improvement has been achieved due to ferroelastic domains switching. The resulting toughness increase has a quadratic relationship with t ' phase volume fraction below a critical value (30 vol%), beyond which it is far smaller to what expected owing to the residual stress being smaller than the ferroelastic coercive stress.